Quality of life measures predict cardiovascular health and physical performance in chronic renal failure patients. - A Rogan; K McCarthy; G McGregor; T Hamborg; G Evans; S Hewins; N Aldridge; S Fletcher; N Krishnan; R Higgins; D Zehnder; S M Ting (PLoS ONE)
Background Patients with advanced chronic kidney disease (CKD) experience complex functional and structural changes of the cardiopulmonary and musculoskeletal system. This results in reduced exercise tolerance, quality of life and ultimately premature death. We investigated the relationship between subjective measures of health related quality of life and objective, standardised functional measures for cardiovascular and pulmonary health. Methods Between April 2010 and January 2013, 143 CKD stage-5 or CKD5d patients (age 46.0±1.1y, 62.2% male), were recruited prospectively. A control group of 83 healthy individuals treated for essential hypertension (HTN; age 53.2±0.9y, 48.22% male) were recruited at random. All patients completed the SF-36 health survey questionnaire, echocardiography, vascular tonometry and cardiopulmonary exercise testing. Results Patients with CKD had significantly lower SF-36 scores than the HTN group; for physical component score (PCS; 45.0 vs 53.9, p<0.001) and mental component score (MCS; 46.9 vs. 54.9, p<0.001). CKD subjects had significantly poorer exercise tolerance and cardiorespiratory performance compared with HTN (maximal oxygen uptake; VO2peak 19.9 vs 25.0ml/kg/min, p<0.001). VO2peak was a significant independent predictor of PCS in both groups (CKD: b = 0.35, p = 0.02 vs HTN: b = 0.27, p = 0.001). No associations were noted between PCS scores and echocardiographic characteristics, vascular elasticity and cardiac biomarkers in either group. No associations were noted between MCS and any variable. The interaction effect of study group with VO2peak on PCS was not significant (ΔB = 0.08; 95%CI -0.28-0.45, p = 0.7). However, overall for a given VO2peak, the measured PCS was much lower for patients with CKD than for HTN cohort, a likely consequence of systemic uremia effects. Conclusion In CKD and HTN, objective physical performance has a significant effect on quality of life; particularly self-reported physical health and functioning. Therefore, these quality of life measures are indeed a good reflection of physical health correlating highly with objective physical performance measures.